Over-employment and the success of combining work and parenthood - N. V. Tonkikh; T. A. Kamarova; T. I. Markova (Модернизация, инновация, развитие, 2024)
Purpose: is to determine the impact of working week length on satisfaction with work-children balance in a gender context.Methods: the empirical data are based on a structured survey of employed Russians raising children under 14 (N = 1449), the final sample size of 826 respondents. The authors’ online survey technology was used. The success of work-children balance was rated on a 10-point scale. Mean satisfaction with work-children balance as a function of parents' working hours was analysed using Mann-Whitney U-test and z-test.Results: sociological assessments show high overemployment among parents of minor children: 56.5% of working fathers and 33.1% of working mothers work over 40 hours a week. The statistical significance of the average estimates of the differentiation of "time for children" satisfaction between overemployed, underemployed and standardly employed parents by working hours revealed gender specificity. Working fathers show no significant difference in the estimated proportions, although overemployed male respondents are 1.6 times less likely to rate the success of their work-children balance as high. Among women, there is a direct correlation: the longer the working week, the lower the average assessment of the success of work-children balance. Women with two or more children of different ages (0–6; 7–14) are the least satisfied with their work-children balance.Conclusions and Relevance: working hours exceeding the normative standards of the RF Labour Code negatively impact women's parental well-being and impede the multi-child parenting as a national demographic goal. It is important to develop mechanisms to encourage employers to reduce overtime for women raising children under 14.